Adopsi dan Konsekuensi Sosial-Ekologis Penggunaan Combine Harvester dalam Pertanian Padi (Studi Kasus di Desa Turusgede) - Anggun Farisyatul Muslimah; Fajar Fajar (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
The labor crisis in the agricultural sector due to the shift in the profession of young rural workers to the industrial and service sectors has led to technological innovations aimed at replacing the role of farm laborers, especially in the harvesting process. As the effectiveness of traditional harvesting methods declines and costs remain high, adopting mechanized tools such as combine harvesters has become a practical alternative for many farmers. This research aims to explain the stages of farmers' adoption of the combine harvester and analyze the consequences of its use on farmers' lives in Turusgede Village, Rembang Sub-district, and Rembang Regency. This research employed a descriptive qualitative approach from March to April 2024. Data were collected through documentation, passive participant observation, and in-depth interviews with nine informants selected via purposive sampling. Data validity was tested using source and technique triangulation. The analysis was performed using Miles and Huberman's interactive model, which includes data condensation, data display, and conclusion drawing. In addition, Everett Rogers' Diffusion of Innovations theory, which consists of knowledge, persuasion, decision, implementation, and confirmation, was used to interpret the dynamics of combined harvester adoption, including economic efficiency, social structure, and environmental impact. The results showed that the use of combine harvesters helped farmers reduce harvesting costs by 30%, speed up harvesting time, and improve grain quality. However, this technology also led to unintended social and environmental consequences, including reduced social interaction among farmers, increased dependence on machine owners, damage to paddy fields, and decreased availability of straw for animal feed.